Polymer latices science and technology - Blackley, D. C. (Chapman & Hall, 1997)
Presents a review of latex science and technology, from background theory and principles, to its applications. This book is suitable for those working in the area of latex science and technology, such as colloid chemists, polymer scientists, and materials processors.